VD_FINDINFO Jug / 2009 / 37 vom 24. September 2009 - VD Tribunal cantonal (2009)
LOI FÉDÉRALE SUR LE CONTRAT D'ASSURANCE, VIOLATION DE L'OBLIGATION D'ANNONCER, PRESCRIPTION | 1 DTAs-AM, 33 LCA, 40 LCA, 46 LCA, 106 LPA-VD